Redistribution, inequality and political participation: Evidence from Mexico during the 2008 financial crisis - Patricia Justino; Bruno Martorano (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
This paper explores the relationship between a large government cash transfer programme, changes in inequality, and political participation in Mexico. The results show that increases in the coverage of the programme during the 2008 financial crisis resulted in greater individual participation in the last presidential elections and in higher individual propensity to vote, particularly for the incumbent party. The programme was particularly effective in increasing political participation among rural and indigenous groups, and had a mitigating effect on participation in presidential elections and the propensity to vote among the urban unskilled. The programme resulted also in reductions in individual participation in protests. Further analysis suggests that these changes were driven by redistributive gains following the changes to the cash transfer programme.
Keywords: D63; D70; D72; H23; I38; 330; conditional cash transfers; inequality; Mexico; protests; voting behaviour